Blockchain and supply chain relations: A transaction cost theory perspective. Issue 4 (October 2019) - Schmidt, Christoph G.; Wagner, Stephan M.
Abstract : Blockchain is projected to be the latest revolutionary technology and is gaining increasing attention from academics and practitioners. Blockchain is essentially a distributed and immutable database that enables more efficient and transparent transactions. The consensus-based record validation can eliminate the need for a trusted intermediary. We utilize the transaction cost theory to create a better understanding of how blockchain might influence supply chain relations, specifically in terms of transaction costs and governance decisions. Conceptually developing a set of six propositions, we argue that blockchain limits opportunistic behavior, the impact of environmental and behavioral uncertainty. Blockchain reduces transaction costs, as it allows for transparent and valid transactions. We explore several areas for future research on how blockchain might shape supply chain management in the future. Highlights: Digitalization influences supply chain practice, and should therefore be integrated as a new boundary condition in PSM research. Blockchain technology influences the prediction of governance structures in the supply chain. Blockchain technology limits opportunistic behavior, environmental and behavioral uncertainty. Blockchain application reduces transaction costs and enables more market-oriented governance structures.